Long COVID and Post-infective Fatigue Syndrome: A Review - Sandler, Carolina X; Wyller, Vegard B B; Moss-Morris, Rona; Buchwald, Dedra; Crawley, Esther; Hautvast, Jeannine; Katz, Ben Z; Knoop, Hans; Little, Paul; Taylor, Renee; Wensaas, Knut-Arne; Lloyd, Andrew R (Open forum infectious diseases, 2021)
Abstract Fatigue is a dominant feature of both acute and convalescent coronavirus disease 2019 (COVID-19) (sometimes termed “long-COVID”), with up to 46% of patients reporting fatigue that lasts from weeks to months. The investigators of the international Collaborative on Fatigue Following Infection (COFFI) conducted a systematic review of post-COVID fatigue and a narrative review on fatigue after other infections, and made recommendations for clinical and research approaches to assessing fatigue after COVID-19. In the majority of COVID-19 cohort studies, persistent fatigue was reported by a significant minority of patients, ranging from 13% to 33% at 16–20 weeks post-symptom onset. Data from the prospective cohort studies in COFFI and others indicate that fatigue is also a prevalent outcome from many acute systemic infections, notably infectious mononucleosis, with a case rate for clinically significant Post-infective fatigue after exclusion of recognized medical and psychiatric causes, ranging from 10%–35% at 6 months. To better characterize post-COVID fatigue, the COFFI investigators recommend the following: application of validated screening questionnaires for case detection; standardized interviews encompassing fatigue, mood, and other symptoms; and investigative approaches to identify end-organ damage and mental health conditions. Fatigue after COVID-19 is common but generally resolves over months, like other postinfective fatigue states. Post-COVID fatigue results from end-organ injury, mental health conditions, or idiopathic post-COVID fatigue. Post-COVID fatigue should be assessed with validated questionnaires, interviews, and protocolized investigations.